Hydrogen production by catalytic hydrolysis of sodium borohydride in batch reactors: new challenges - Ferreira, M. J. F. (2011)
The present manuscript faces the study of H2 generation and storage from catalytic hydrolysis of sodium borohydride (NaBH4) under pressure. We revisit several works on this topic developed (or under development) by our team in the last four years on some of the most critical issues in this research area, namely catalyst durability/reutilization, gravimetric hydrogen storage density and recyclability. New results are also presented. Hydrogen generation rates and yields and hydrogen storage capacities can be augmented to reach 6 wt%, by adding small amounts of an organic polymer (CMC) to the classic NaBH4 hydrolysis, performed with stoichiometric amount of water in a batch reactor with a conical bottom shape and in the presence of Ni-Ru based catalyst, reused from 300 times. Sodium tetrahydroxoborate, NaB(OH)4), was produced in the presence of CMC additive, and did not show crystalline water in its crystal structure. This latter finding has potential to reduce recycling costs of NaBO2 back to NaBH4 and also increase the overall storage density of systems based on NaBH4 as hydrogen carrier.